AUDIT EFFICIENCY AND ITS ROLE IN ACHIEVING THE SUSTAINABILITY OF FINANCIAL REPORTING UNDER IFRS - Abdulqudoos Hussein Mohammed; Mohammed A.ALHasan Mohammed (Jurnal Ekonomi, Bisnis dan Pendidikan, 2026)
The study aimed to identify the impact of auditing as a profession that seeks to create value for the organization and confidence in financial data on the sustainability of international financial reporting in accordance with International Financial Reporting Standards (IFRS) and the extent of its impact on the efficiency of the organization. To achieve the research objectives, the descriptive and analytical approach was used, which relies on studying reality or phenomena and is concerned with describing them accurately. The questionnaire was used to collect data, and statistical analysis, regression analysis, correlation, and validity and reliability testing were employed. In addition, available references, periodicals, and the Internet were used to cover the theoretical aspect. The research community consists of Iraqi banks listed on the Iraq Stock Exchange. Based on the analysis of the opinions of the study sample, the responses to questions (1, 2, 4, 6, 7, 10) received the highest acceptance rate regarding the ability of International Accounting Standards to influence the Iraqi environment, whether among management, investors, or the public, with a strong acceptance level on the Likert scale. Meanwhile, Question (9), which relates to whether the experience, academic, and professional standing of the accounting staff within the bank positively influences the sustainable financial reporting process, received the lowest arithmetic mean of 3.24. Based on these findings, the study recommended that the administration of banks must keep pace with compliance with International Financial Reporting Standards (IFRS) by strengthening commitment to the auditing profession and activating its role through expanding the auditor’s framework to include analyzing the economic and regulatory conditions of the bank, which can have an important impact on its continuity, thus contributing to creating its sustainability.